ChemInform Abstract: Syntheses of Fused Tetracyclic Quinolines via Ugi‐Variant MCR and Pd‐Catalyzed Bis‐Annulation. Issue 23 (10th June 2014) - Che, Chao; Yang, Bo; Jiang, Xianlong; Shao, Taofeng; Yu, Zhixiong; Tao, Chuanye; Li, Song; Lin, Shuo
Abstract A diversity‐oriented synthesis of fused tetracyclic 6, 11‐dihydroquinoxalino[2, 3‐b]quinolines is described via sequential Ugi‐variant multicomponent reaction and Pd‐catalyzed bis‐annulation in a one‐pot process.